2020
DOI: 10.1016/j.vas.2019.100067
|View full text |Cite
|
Sign up to set email alerts
|

Destination of corpus luteum in postpartum clinical endometritis cows and factors affecting self-recovery

Abstract: Highlights The most cyclic clinical endometritis cows revealed new CL two weeks after clean test. The uterus of most of cyclic clinical endometritis cows was clean 14 days after 30 ± 3 days postpartum. About two third of clinical endometritis cows with persistent CL remained infected after second examination and considered as pyometric cows. Concentration of some metabolic or steroid hormones and production and reproduction factors influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(61 reference statements)
0
5
0
3
Order By: Relevance
“…Furthermore, in recent years, a novel Corynebacterium endometrii sp. nov., has also been isolated from the uterus of a cow with endometritis [88], whereas data in other studies according to Miranda-Casoluengo et al [55] and Wang et al [89] also confirmed a higher relative abundance of Bacteroidetes and Fusobacterium in cows that developed CE.…”
Section: Clinical and Sub-clinical Endometritismentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, in recent years, a novel Corynebacterium endometrii sp. nov., has also been isolated from the uterus of a cow with endometritis [88], whereas data in other studies according to Miranda-Casoluengo et al [55] and Wang et al [89] also confirmed a higher relative abundance of Bacteroidetes and Fusobacterium in cows that developed CE.…”
Section: Clinical and Sub-clinical Endometritismentioning
confidence: 80%
“…This highlights the importance of monitoring the cyclicity of cows with endometritis to diagnose early symptoms for treatment. However, the CL on the cow's ovary and its fate may affect the recovery from severe clinical endometritis [88]. Therefore, the size and location of the reproductive tract affected self-healing from clinical endometritis.…”
Section: Clinical and Sub-clinical Endometritismentioning
confidence: 99%
“…For many years, the morphology and function of bovine ovarian lutein structures have been the subject of intense research and discussion (Costa et al, 2020;Mogheiseh et al, 2020;Walusimbi and Pate, 2014;Xavier et al, 2012). The cellular composition of the CL has not been definitively determined (Fields and Fields, 1996;Fields et al, 1992;Parkinson et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The functional value of luteocyte cytoplasmic granules have not been established (Jaśkowski, 2019;Vargas et al, 2015). The available papers describe differences in the CL of pregnancy, ovary cycle and endometritis (Mogheiseh et al, 2020;Sawyer, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Наявна залежність перебігу інволюційних процесів від продуктивності корів і тривалості сухостійного періоду: негативно впливає не лише короткий (менше 30 діб), але й тривалий (більше 120 діб) сухостійний період. За високої молочної продуктивності темпи інволюції знижуються [16][17][18][19][20].…”
Section: дніпровський державний аграрно-економічний університетunclassified